The Lived Experience of Graduate Entry Nursing Students’ Development of Empathy in Clinical Practice: A Hermeneutic Phenomenological Study - Badger, Amanda (Auckland University of Technology, 2026)
In this study, I aimed to understand the lived experiences of Graduate Entry Nursing (GEN) students and their development of empathy in clinical practice in Aotearoa New Zealand. Empathy is a fundamental nursing quality that fosters trust, connection, and therapeutic relationships between the health professional, health consumers and their whānau (family). Empathy is a nursing quality that can be both taught and learnt, yet the experience of developing empathy for GEN students had not been researched. As such, this study sought to understand the lived experiences of GEN students in Aotearoa New Zealand and how they experience the development of empathy, a fundamental quality of nursing practice, in clinical practice. The research methodology, hermeneutic phenomenology, influenced by the works of Heidegger, Gadamer, van Manen and Benner, was selected due to its appropriateness for this study. Hermeneutic phenomenology seeks to understand the lived experience of a phenomenon, which in this case was the development of empathy. Seven GEN students volunteered to participate in this study. One-to-one interviews were conducted, recorded, and transcribed for meaning-making using van Manen's six-step process. The findings from this study revealed three main themes from the students' experiences. These findings offer valuable insights for nurse educators, preceptors, tertiary institutes, and the nursing profession. This study contributes to a broader understanding of nursing students' experience of empathy development in clinical practice. It provides insights crucial for tailoring support to GEN students and future cohorts. This thesis is a testament to the transformative power of pausing, listening, understanding, and taking the time to connect with others through shared humanity.